Corporate Creativity Socialization Program: Preventing Impulsive Buying and Building Habits in Families - Alfin Nur Arifah; Dheri febiyani Lestari; Rizky Ridwan; Aditia Abdurachman; Rina Madyasari (LPPM Universitas Muhammadiyah Tasikmalaya, 2024)
The